Re-habitar a cidade: estudo de caso de uma residência terapêutica mista na cidade de São Paulo, como dispositivo promotor da cidadania - Silva, Tammya Tercia Oliveira Ribeiro da (2011)
The transfer of psychiatric hospitals care to community care of people affected by mental disorders is the current proposal from Psychiatric Reform. To keep those people suffering from mental disorders institutionalized is to withdraw of their constitution's right of its subjectivity. Among the devices of care in the community, we have the Therapeutic Residential Services (TRS), homes that provides care for a maximum of eight people recent grads from psychiatric hospitals, who were under long hospitalization, aiming the reconstruction of their identity. Objective: To analyze the autonomy and dependency process promoted by the TRS device in a year of its implementation. Method: it is a qualitative research with participant observation. We used the following tools to describe the implementation of the joint residence: the books ATA, the researcher's notebook, the direct observation in the residence and interviews with users, community caregivers and coordinator. Results: From the data analysis we took three broad categories of autonomy and dependency of people who were under a long period of institutionalization, which must be invested in rehabilitative stocks: Self-Concept, Affective Relations, and Social Integration. These categories analysis allowed verifying that the TRS users showed improvement in autonomy, social interaction, global functioning and quality of life. The deinstitutionalization implies the existence of new community services, which requires the presence of qualified professionals and effective rehabilitation programs. Conclusion: Despite of the difficulties for the TRS implementing, it has an important role in the process of emotional reframing and social reintegration, where users are able to establish community exchanges and to conduct social activities suggesting autonomy acquisition. We verify then the importance of considering intervention strategies that enable these people gain a greater autonomy, where they can reframe the everyday, as the propositions of the Psychiatric Reform Movement